Prevalence of toxoplasmosis in Iraqi patients with diabetic type 2 - Sarah Ali Saeed; Israa Kasim Al-Aubaidi (Romanian Journal of Infectious Diseases)
Background. The obligate intracellular protozoan parasite Toxoplasma gondii is a member of the phylum Apicomplexa. In people with impaired immune systems, it can result in opportunistic infections. Diabetes mellitus is regarded as a metabolic disease that raises the host's vulnerability to and risk from several infections, including T. gondii infection. The main object of this study is to ascertain the toxoplasmosis seroprevalence and correlation among Iraqi patients with type 2 diabetes. Methods. The level of Toxoplasma antibodies IgG, IgM, and IgA was measured in 109 samples of Iraqi diabetes type 2 patients using immunochromatography rapid test, CMIA, and ELISA. Eighty samples, considered to be a healthy control group, were collected from a private laboratory in Baghdad, Iraq, between March 2022 and June 2022, with an age range of 15 to 85 years. Results. Comparing the diabetes patient group to the non-diabetic control group, the results showed that the diabetic patient group had the highest mean glucose levels in their fasting test (174.55 ± 3.96 mg/dL), random test (216.89 ± 4.96 mg/dL), and HbA1C (7.1 ± 0.178), respectively. Furthermore, the study demonstrated that, in an immunochromatography fast test, the group of diabetic patients had the largest distribution of IgG anti-Toxoplasma when compared to the non-diabetic control group. Additionally, all samples were seronegative for anti-Toxoplasma IgM and IgA, with significant differences in CMIA and ELISA. However, 51/109 (46.79%) and 30/80 (37.5%) of the diabetes group and the non-diabetic group, respectively, showed seropositive for anti-Toxoplasma IgG. Conclusion. This study found that no acute toxoplasmosis detected in the studied cases while chronic toxoplasmosis detected among diabetic type 2 patients.